RELIGIOUS REFERENCES IN ROMANIAN AND HUNGARIAN NEWS AND COMMENTS ON THE REFUGEE CRISIS. - Vincze, Hanna Orsolya (Journal for the Study of Religions & Ideologies)
Public discussions of the recent rise in the number of refugees and asylum seekers, commonly referred to as "the refugee crisis" employ recurrent references to religion. This paper investigates the salience of religion in Romanian and Hungarian online news and comments. It aims to contribute to better understanding the role religion plays in the public understanding of the refugee crisis, and also to the wider issue of the role of religion in public discussions. It also aims to identify the specific local discourses that the local audiences revert to when making sense of and commenting on foreign news. The analysis applies corpus linguistic and discourse analytical approaches to a constructed week sample of Romanian and Hungarian news and their comments. The main referential strategies identified with regard to religion are generic religion, religion as difference, visible religion and religious threats. Similarities of the two news cultures point to continuities that transcend national boundaries, and are connected to wider trends in the role of religion in the public understanding of the refugee crisis. References to religion are also shown to intersect with local political discourses. In the wider context of the European public sphere, and the debates over its secular nature or desecularization, the results suggest that the mediatization and politization of religion in the context of the refugee crisis needs to be understood as a "secular return" rather than desecularization.